Soft porcelain material capable of preventing water and fire and preparation method of soft porcelain material
By using modified polymer emulsions and modified inorganic nanomaterials in soft porcelain materials, combined with inorganic powder and waterproofing agents, the problems of high water absorption and poor flame retardant performance of existing soft porcelain materials are solved, and the effect of water and fire protection is achieved.
Patent Information
- Application Number
- CN202411516646.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-03-11
AI Technical Summary
The water absorption rate of existing soft porcelain materials is too high, resulting in reduced durability and difficult to meet customer requirements.
Modified polymer emulsions and modified inorganic nanomaterials are used to improve the hydrophobicity and flame retardant properties of the material through physical blending and chemical coupling reactions, and combined with inorganic powder and waterproofing agents, soft porcelain materials with water and fire protection are prepared.
It significantly reduces the water absorption rate of the material, improves its durability and flame retardant properties, and meets the needs of water and fire protection.
Smart Images

Figure CN119591352A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water- and fire-resistant soft porcelain materials, and in particular to a water- and fire-resistant soft porcelain material and a preparation method thereof. Background Art
[0002] The water absorption rate of the soft porcelain materials currently available on the market is too high, basically in the range of 10%-15%, which is difficult to achieve the water absorption rate as low as 3% or below required by the soft porcelain industry standard. The long-term erosion of soft porcelain materials by water reduces the durability of soft porcelain materials, thereby reducing the service life of soft porcelain materials. At the same time, the flame retardant properties of soft porcelain materials are also difficult to meet customer requirements. Summary of the invention
[0003] The main purpose of the present invention is to provide a water- and fire-resistant soft porcelain material and a preparation method thereof, aiming to solve the problem that the existing soft porcelain material has poor water- and fire-resistant properties.
[0004] To achieve the above-mentioned purpose, the present invention proposes a soft porcelain material with dual water and fire resistance, wherein the raw materials of the soft porcelain material with dual water and fire resistance include the following components: inorganic powder, modified polymer emulsion, surfactant, modified inorganic nanomaterial, curing agent, dispersant, film-forming aid, fiber and waterproofing agent, wherein the preparation step of the modified polymer emulsion includes blending at least two polymer emulsions to obtain a mixture, and the mixture is mixed with the surfactant to produce a coupling reaction; the preparation step of the modified inorganic nanomaterial includes modifying the inorganic nanomaterial with a fluorinating agent.
[0005] In one embodiment, the raw materials of the water- and fire-resistant soft porcelain material are calculated by weight, and the raw materials of the water- and fire-resistant soft porcelain material include the following components: 100-105 parts of inorganic powder, 12-25 parts of modified polymer emulsion, 0.3-9 parts of surfactant, 5-10 parts of modified inorganic nanomaterials, 0.1-0.4 parts of curing agent, 0.1-0.4 parts of dispersant, 0.1-0.4 parts of film-forming aid, 0.1-0.4 parts of fiber and 0.1-0.4 parts of waterproofing agent.
[0006] In one embodiment, the inorganic powder includes quartz powder, kaolin, diatomaceous earth, alumina, waste residue, modified aluminum hydroxide and the modified magnesium hydroxide; and / or,
[0007] The modified polymer emulsion includes at least two of polyurethane emulsion, acrylic emulsion and EVA emulsion; and / or,
[0008] The surfactant includes at least one of a titanate coupling agent, an aluminate coupling agent, a silane coupling agent, and liquid paraffin; and / or,
[0009] The modified inorganic nanomaterial includes at least one of nano calcium carbonate, nano titanium dioxide and nano silicon dioxide; and / or,
[0010] The curing agent includes aziridine or polycarbodiimide; and / or,
[0011] The dispersant comprises SN 5040; and / or,
[0012] The film-forming aid includes alcohol ester 12; and / or,
[0013] The fibers include polypropylene fibers modified by coupling agents, carbon fibers modified by coupling agents, and glass fibers modified by coupling agents; and / or,
[0014] The waterproofing agent includes an organic silicon waterproofing agent.
[0015] In one embodiment, the inorganic powder includes waste residue, and the waste residue includes fly ash microbeads, mineral powder or silica fume.
[0016] In one embodiment, the inorganic powder further comprises an alkaline activator, and the amount of the alkaline activator added is 2-4% of the inorganic powder; and / or,
[0017] The quartz powder, the kaolin, the diatomaceous earth, the alumina, the waste residue, the modified aluminum hydroxide and the modified magnesium hydroxide, wherein the mass ratio of the quartz powder, the kaolin, the diatomaceous earth, the alumina, the waste residue, the silica fume, the modified aluminum hydroxide and the modified magnesium hydroxide is (2-4): (2-3): (2-3): (1-2): (1-3): (1-2): (0-1).
[0018] In one embodiment, the steps include:
[0019] S10, mixing and heating the inorganic powder and the surfactant to obtain a modified inorganic powder;
[0020] S20, mixing the modified polymer emulsion with the modified inorganic nanomaterial to obtain a first emulsion;
[0021] S30, mixing the first emulsion with a curing agent, a dispersant, a film-forming aid, fibers and a modified inorganic powder to obtain a second emulsion;
[0022] S40, drying the second emulsion and demoulding to obtain a water- and fire-resistant soft ceramic material.
[0023] In one embodiment, in step S10, the heating temperature is 70-150°C.
[0024] Step S40 includes: drying the second emulsion at 40-50° C. for 5 hours, adjusting the temperature to 80-150° C. for baking for 4-10 hours, and demolding to obtain a water- and fire-resistant soft ceramic material.
[0025] The technical solution of the present invention improves the physical properties of both by modifying the polymer emulsion and the modified inorganic nanomaterial in the soft porcelain material with dual water and fire protection, and physically blending the modified polymer emulsion into at least two polymer emulsions. The organic groups of the carboxyl type are oriented to the surface of the target mixture after the surfactant is added, and can be combined with the organic functional groups to generate hydrophobic chemical bonds to form a modified modified polymer emulsion. The inorganic nanomaterial can effectively adsorb free electrons after being modified by a fluorinating agent, weakening the electric field distortion caused by the introduction of the nanomaterial, and reducing the average charge density inside the sample. The dual modification of the polymer emulsion and the inorganic nanomaterial is conducive to further improving the hydrophobicity of the surface, and combined with the flame retardancy of the inorganic powder, so as to obtain the soft porcelain material with dual water and fire protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0027] Figure 1 The present invention provides a schematic diagram of the preparation process of a water and fire resistant soft porcelain material embodiment.
[0028] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.
[0031] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, if "and / or" or "and / or" appears in the full text, its meaning includes three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0032] The water absorption rate of the water-proof and fire-proof soft porcelain materials currently available in the market is too high, basically in the range of 10%-15%, which is difficult to achieve the water absorption rate as low as 3% or below required by the soft porcelain industry standard. The long-term erosion of water on the water-proof and fire-proof soft porcelain materials reduces the durability of the water-proof and fire-proof soft porcelain materials, thereby reducing the service life of the water-proof and fire-proof soft porcelain materials. At the same time, the flame retardant properties of the water-proof and fire-proof soft porcelain materials are also difficult to meet customer requirements.
[0033] In view of this, the present invention proposes a soft porcelain material that is both water and fire resistant. The raw materials of the soft porcelain material that is both water and fire resistant include the following components: inorganic powder, modified polymer emulsion, surfactant, modified inorganic nanomaterial, curing agent, dispersant, film-forming aid, fiber and waterproofing agent, wherein the preparation step of the modified polymer emulsion includes blending at least two polymer emulsions to obtain a mixture, and the mixture is mixed with the surfactant to produce a coupling reaction; the preparation step of the modified inorganic nanomaterial includes modifying the inorganic nanomaterial with a fluorinating agent.
[0034] The technical solution of the present invention improves the physical properties of both by modifying the polymer emulsion and the modified inorganic nanomaterial in the soft porcelain material with dual water and fire protection, and physically blending the modified polymer emulsion into at least two polymer emulsions. The organic groups of the carboxyl type are oriented to the surface of the target mixture after the surfactant is added, and can be combined with the organic functional groups to generate hydrophobic chemical bonds to form a modified modified polymer emulsion. The inorganic nanomaterial can effectively adsorb free electrons after being modified by a fluorinating agent, weakening the electric field distortion caused by the introduction of the nanomaterial, and reducing the average charge density inside the sample. The dual modification of the polymer emulsion and the inorganic nanomaterial is conducive to further improving the hydrophobicity of the surface, and combined with the flame retardancy of the inorganic powder, so as to obtain the soft porcelain material with dual water and fire protection.
[0035] It should be noted that, in the technical scheme of the present invention, the inorganic nanomaterials and polymer emulsions in the water- and fire-resistant soft porcelain material are modified to obtain the water- and fire-resistant soft porcelain material. Specifically, the surfactant derived from citric acid usually utilizes hydroxyl groups to construct the hydrophobic group of the surfactant, and introduces long-chain alkyl groups or connecting groups thereon. The adjacent carboxyl groups in its molecular structure are hydrophilic groups, and the component is lauroyl citrate. This type of substance has the characteristics of both chelating agents and surfactants, and has the advantages of low foaming and good emulsification ability.
[0036] In an embodiment of the present invention, the raw materials of the water- and fire-resistant soft porcelain material are calculated by weight, and the raw materials of the water- and fire-resistant soft porcelain material include the following components: 100-105 parts of inorganic powder, 12-25 parts of modified polymer emulsion, 0.3-9 parts of surfactant, 5-10 parts of modified inorganic nanomaterial, 0.1-0.4 parts of curing agent, 0.1-0.4 parts of dispersant, 0.1-0.4 parts of film-forming aid, 0.1-0.4 parts of fiber and 0.1-0.4 parts of waterproofing agent.
[0037] It should be noted that inorganic powder can provide the main structural basis of the soft ceramic material that is both water and fire resistant, affecting the hardness, strength and wear resistance. This ratio ensures sufficient basic material to achieve the required structural strength and stability; modified polymer materials can enhance the flexibility, elasticity and adhesion of the soft ceramic material that is both water and fire resistant, so that it can adapt to different application requirements, ensure the flexibility and adhesion of the soft ceramic material that is both water and fire resistant after hardening, and at the same time do not affect the overall strength of the material; surfactants can improve the dispersion and uniformity of the ingredients, avoid agglomeration of the ingredients in the material, ensure the appropriate amount of surfactant to optimize the mixing and dispersion of the ingredients, but not excessively affect the material performance; modified inorganic nanomaterials mainly increase the viscosity of the polymer material, reduce the porosity of the surface, and enhance its density, thereby reducing the intrusion of moisture into the soft ceramic material that is both water and fire resistant, and ensuring that the nanomaterial can effectively Enhance performance while avoiding excessive amounts that lead to increased material costs or unstable performance; Curing agent can accelerate the curing process of the material, transforming it from liquid to solid, ensuring the right amount of curing agent to achieve the expected curing speed and completeness without affecting other properties of the material; Dispersant helps disperse other components, prevents components from settling or agglomerating, ensures uniform distribution of components, and does not interfere with the effects of other components; Film-forming aids help form a smooth and uniform surface film, increase the appearance quality of the material, ensure that a good film layer can be formed on the surface of the material, and enhance aesthetics and functionality; Fibers can improve the mechanical strength and durability of the material, increase tensile and crack resistance, and the right amount of fiber can enhance the strength and toughness of the material without affecting the processability of the material; Waterproofing agent can improve the waterproof performance of the material, reduce the impact of moisture on the material, and ensure that the material has sufficient waterproof performance, but does not affect other properties. The purpose of these ratios is to maintain the water-proof and fire-proof properties of soft porcelain materials while ensuring other properties, such as flame retardancy and wear resistance, to meet different application requirements and environmental conditions.
[0038] In an embodiment of the present invention, the inorganic powder includes quartz powder, kaolin, diatomaceous earth, alumina, waste residue, modified aluminum hydroxide and modified magnesium hydroxide, wherein the alumina is preferably 80 mesh, and the inorganic powder mixture of the above components is selected to achieve the required structural strength and stability, and the raw materials of modified aluminum hydroxide and modified magnesium hydroxide, magnesium hydroxide and aluminum hydroxide, can be purchased on the market. The specific modification step includes: heating the magnesium hydroxide and aluminum hydroxide at 60°C respectively, adding silane coupling agent KH550 dropwise, adding it to a mixed solution of water, oxalic acid and ethanol to hydrolyze the silane coupling agent KH550, and then spraying it on the surface of the powder, stirring and grinding and sieving to modify the magnesium hydroxide and modified aluminum hydroxide respectively, which can improve the flame retardancy.
[0039] Among them, the inorganic powder includes quartz powder, kaolin, diatomaceous earth, alumina, waste residue, modified aluminum hydroxide and modified magnesium hydroxide, wherein the mass ratio of the quartz powder, the kaolin, the diatomaceous earth, the alumina, the waste residue, the modified aluminum hydroxide and the modified magnesium hydroxide is (2-4): (2-3): (2-3): (1-2): (1-3): (1-2): (0-1), specifically, the mass ratio of quartz powder, kaolin, diatomaceous earth, alumina, waste residue, modified aluminum hydroxide and modified magnesium hydroxide is 4:3:3:2:3:2:1, which has a better effect. The modified polymer emulsion includes at least one of polyurethane emulsion, acrylic emulsion and EVA emulsion. As the base material of the soft ceramic material that is both water and fire resistant, it is preferably a mixture of polyurethane emulsion and acrylic emulsion, wherein the addition amount of polyurethane emulsion is 2% to 5% of the modified inorganic nano powder, and the addition amount of acrylic emulsion is 10% to 15% of the modified inorganic nano powder. Within the above range, the performance is better.
[0040] The surfactant includes at least two of titanate coupling agent, aluminate coupling agent, silane coupling agent, and liquid paraffin. Here, coupling agent refers to a class of substances that can improve the interface characteristics between inorganic powder and polymer material, and there are two functional groups in its molecular structure: one can react chemically with the polymer matrix or at least have good compatibility; the other can form a chemical bond with the inorganic powder. The coupling agent can improve the interface performance between the polymer material and the inorganic powder, improve the adhesion of the interface, and improve the performance of the filled or reinforced polymer material. Preferably, the use of three composite coupling agents has advantages over a single coupling agent; for example: the hydrophilic group in kh570 and the lipophilic group in titanate, under a certain component ratio, the two reach a balance of hydrophilic and lipophilic values, thereby generating a synergistic effect.
[0041] Furthermore, the titanate coupling agent of the present application can be used in the general formula: (RO) MTi(OXR'Y)n (n = 2, 3), where RO- is a hydrolyzable short carbon chain alkoxy group, which can react with the surface hydroxyl group of inorganic substances to achieve the purpose of chemical coupling, -OX can be a carboxyl group, an alkoxy group, a sulfonic acid group, a phosphorus group, etc. These groups are very important and determine the special properties of titanate, R' is a long carbon bond alkane group, which is relatively soft and can bend and hide with organic polymers to improve the compatibility of organic and inorganic substances and improve the impact strength of the material, and Y is a hydroxyl group, an amino group, an epoxy group or a double bond group, etc. These groups are connected to the ends of the titanate molecules and can react chemically with the organic polymer to combine together. Specifically, the surfactant in the present application preferably adopts a titanate coupling agent, which can undergo ester transfer and cross-linking with the carboxyl group, ester group, etc. in the polymer solution, resulting in cross-linking of titanate, inorganic powder and organic polymer, thereby increasing the viscosity of the system. Therefore, it can cross-link with the polymer solution to increase the cross-linking characteristics. On the other hand, it can also chemically bond with the modified polymer emulsion to modify the modified polymer emulsion and improve the durability.
[0042] The modified inorganic nanomaterial includes at least one of nano calcium carbonate, nano titanium dioxide and nano silicon dioxide; using the above components as modified inorganic nanomaterials can improve the density and mechanical properties of the material. Preferably, a mixture of nano calcium carbonate, nano titanium dioxide and nano silicon dioxide has the best effect, and the ratio of the two is 1:2:1, which is better. The curing agent includes aziridine or polycarbodiimide to promote the cross-linking and curing of the material.
[0043] The dispersant includes dispersant SN 5040, which is a polycarboxylate sodium salt type dispersant, has low foaming property, improves the fluidity of the coating, and has the performance of stabilizing the viscosity of the slurry.
[0044] The film-forming aid includes alcohol ester 12, also known as polydimethylsiloxane / PEG-12 dimer. It is obtained by the chemical reaction of polydimethylsiloxane and polyethylene glycol (PEG), and helps the modified polymer emulsion to form a uniform and dense film on the surface of the material.
[0045] The fibers include polypropylene fibers modified by coupling agents, carbon fibers modified by coupling agents, and glass fibers modified by coupling agents. After being modified by coupling agents, the fibers have increased tensile strength, toughness, and crack resistance.
[0046] The waterproofing agent includes an organic silicon waterproofing agent, which imparts excellent waterproofing properties to the material, reduces the water absorption rate of the material, and prevents moisture penetration and erosion of the material.
[0047] In some embodiments, the mineral powder includes fly ash microbeads, mineral powder or silica ash. The fly ash microbeads can reduce the viscosity of inorganic materials, improve fluidity, and thus improve workability. The use of mineral powder can utilize waste, and has environmental protection factors. It can be used as a filler to reduce the cost of materials and improve the environmental performance of materials.
[0048] In some embodiments, the inorganic powder also includes an alkaline activator, and the added amount of the alkaline activator is 2-4% of the inorganic powder, wherein the alkaline activator is used to activate the inorganic components in the material, promote their reaction, and improve the early strength and curing speed of the material. Preferably, the added amount of the alkaline activator is optimally 3% of the mass of the mixture of inorganic powders.
[0049] The inorganic powder includes quartz powder, kaolin, diatomaceous earth, alumina, mineral powder, modified aluminum hydroxide and modified magnesium hydroxide, wherein the mass ratio of the quartz powder, the kaolin, the diatomaceous earth, the alumina, the waste residue, the modified aluminum hydroxide and the modified magnesium hydroxide is 4:3:3:2:3:2:1. At the above mass ratio, the performance of the inorganic powder is better.
[0050] In some embodiments, the steps include:
[0051] S10, mixing and heating the inorganic powder and the surfactant to obtain a modified inorganic powder;
[0052] S20, mixing the modified polymer emulsion with the modified inorganic nanomaterial to obtain a first emulsion;
[0053] S30, mixing the first emulsion with a curing agent, a dispersant, a film-forming aid, fibers and a modified inorganic powder to obtain a second emulsion;
[0054] S40, drying the second emulsion and demoulding to obtain a water- and fire-resistant soft ceramic material.
[0055] The modified inorganic powder, modified polymer emulsion and modified inorganic nanomaterial are mixed in the above preparation method to prepare a soft porcelain material that is both water and fire resistant.
[0056] In one embodiment, in step S10, the heating temperature is 70-150°C.
[0057] Step S40 includes: drying the second emulsion at 40-50° C. for 5 hours, adjusting the temperature to 80-150° C. for baking for 4-10 hours, and demolding to obtain a water- and fire-resistant soft ceramic material.
[0058] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0059] In the following examples, the quartz powder was purchased from Runjia Quartz Sand Factory;
[0060] The kaolin was purchased from Tianjin Kemeiou;
[0061] The silica fume was purchased from Shanghai Chenqi Chemical Technology Co., Ltd.
[0062] The aluminum oxide was purchased from Gongyi Chaoyue Filter Material Factory;
[0063] The mineral powder was purchased from Henan Borun Casting Materials Co., Ltd.
[0064] The fly ash microbeads are floating beads purchased from Henan Borun Casting Materials Co., Ltd.
[0065] Polypropylene fiber was purchased from Changsha Ningxiang Building Materials Co., Ltd. HC15;
[0066] The silica fume was purchased from Gongyi Yuannuo Environmental Protection Engineering Co., Ltd.
[0067] The modified aluminum hydroxide was purchased from Yangzhou Dilan Co., Ltd., Jiangsu Province;
[0068] The modified magnesium hydroxide was purchased from Wuxi Yatai United Chemical Co., Ltd., Jiangsu Province;
[0069] The curing agent is polycarbodiimide;
[0070] Dispersant SN 5040;
[0071] The film-forming aid is alcohol ester 12;
[0072] The fiber is made of polypropylene fiber modified by coupling agent:
[0073] The waterproofing agent is an organic silicon fluorine waterproofing agent, model YC265 waterproofing agent from Guangzhou Yuchuang Company;
[0074] The fluorocarbon emulsion was F13-0801 from Yoshida Chemical.
[0075] Example
[0076] The specific components of Examples 1 to 5 are shown in Table 1.
[0077] Table 1 Mass fractions of each raw material in Examples 1-5 and Comparative Examples 1-2
[0078]
[0079]
[0080] In Table 1, “\” indicates that the component is not contained.
[0081] Example 6
[0082] A method for preparing a water- and fire-resistant soft porcelain material comprises the following steps:
[0083] S10, first weigh: 500g of quartz powder, 200g of kaolin, 100g of diatomaceous earth, 100g of alumina, 50g of mineral powder, 20g of modified magnesium hydroxide, 30g of modified aluminum hydroxide, mix to obtain inorganic powder, and control the temperature at 70-150 degrees Celsius for dynamic heating, and continue to add 3% by weight of water glass, whose modulus is 2.5 and 20g of KH550 to the above inorganic powder, mix and heat to obtain modified inorganic powder;
[0084] S20, mixing 300 g of the modified polymer emulsion with 6 g of the modified inorganic nanomaterial to obtain a first emulsion;
[0085] S30, mixing the first emulsion with 15 g of polycarbodiimide (a specific product of a curing agent), 9 g of a dispersant SN5040, 9 g of an alcohol ester 12, 18 g of a coupling agent-modified polypropylene fiber, and the modified inorganic powder obtained in step S10 to obtain a second emulsion;
[0086] S40, placing the second emulsion into a vacuum drying oven and drying it at 40 degrees Celsius for 5 hours, then adjusting the temperature to 120 degrees Celsius and baking it for 4 hours, and demolding to obtain a soft ceramic material that is both water-resistant and fire-resistant.
[0087] The preparation steps of the modified polymer emulsion include: firstly, 60g of polyurethane emulsion and 240g of EVA emulsion are blended in a ratio of 1:4, and 18g of silane coupling agent KH570, 10g of titanate coupling agent, 200g of deionized water and 15g of waterproofing agent are added and mixed evenly under strong mechanical shear force to obtain the modified polymer emulsion, and 300g of the modified polymer emulsion is used in Example 6;
[0088] The preparation steps of the modified inorganic nanomaterial include: adding 3g of nano-silicon dioxide to 2g of fluorocarbon emulsion to obtain the modified inorganic nanomaterial, and then taking 6g of it for Example 6;
[0089] Modified magnesium hydroxide: Heat 30g of magnesium hydroxide at 60°C, add 0.3g of silane coupling agent KH550, add a mixed solution of 15g water, 1g oxalic acid and 15g ethanol to hydrolyze, spray it on the powder surface, stir and grind and sieve to modify the magnesium hydroxide respectively, and then take 20g of the modified magnesium hydroxide for Example 6.
[0090] Modified aluminum hydroxide: Heat 30g of aluminum hydroxide at 60°C, add 0.45g of silane coupling agent KH550, add it into a mixed solution of 15g water, 1g oxalic acid and 15g of anhydrous ethanol for hydrolysis, spray it on the powder surface, stir and grind and sieve to modify the magnesium hydroxide respectively, and then take 30g of modified aluminum hydroxide for Example 6.
[0091] Comparative Example 1
[0092] The EVA emulsion was omitted from the preparation steps of the modified polymer emulsion, and the rest were the same as in Example 6, as shown in Table 1.
[0093] Comparative Example 2
[0094] The modified inorganic nanomaterial is replaced by nano silicon dioxide instead of being modified by carbon fluoride emulsion. The rest is different from Example 6, as shown in Table 1.
[0095] Performance Testing
[0096] The water- and fire-resistant soft ceramic materials of Examples 1-6 and Comparative Examples 1-2 were tested for apparent relative density, wear resistance (load 5N), water absorption, contact angle measurement, surface scratch resistance and flame retardancy.
[0097] Apparent relative density: Tested in accordance with GB / T3810.3-2016;
[0098] Wear resistance (load 5N): refer to GB / T9867-2008;
[0099] Water absorption rate: Tested in accordance with GB / T3810.3-2016;
[0100] The contact angle is measured by a surface contact angle tester;
[0101] Flame retardancy: Referring to GB / T 14833-2020, the test results are shown in Table 2.
[0102] Table 2 Performance test results of Examples 1-5 and Comparative Examples 1-3
[0103]
[0104] In Table 2, “-” means the item was not tested.
[0105] It can be seen from Table 2 that compared with the embodiment, Comparative Example 1 is modified by a single polyurethane emulsion. In Example 1, since the polyurethane emulsion (PU) contains more carbamate, urea, ester, ether and other groups, it can form hydrogen bonds with the hydroxyl groups on the polyvinyl alcohol in the VAE film during the film formation process. This effect promotes the compatibility of VAE / PU, increases the degree of physical crosslinking of the film, and reduces the dissolution of polyvinyl alcohol by water. Therefore, the water absorption rate decreases, the contact angle decreases, and the wear resistance of Comparative Example 1 is poor; and since Comparative Example 1 does not use modified aluminum hydroxide and modified magnesium hydroxide, the flame retardancy is reduced to level 2, and there are a few scratches.
[0106] Compared with the embodiment, Comparative Example 2 uses ordinary inorganic nanomaterials and has not been modified by fluorocarbon emulsion. The surface ion hydrophobicity of the embodiment is greatly improved due to the use of fluorocarbon emulsion, and the water absorption rate is low. The advantages of fluorocarbon emulsion: because the fluorocarbon bond has a higher bond energy and lower polarity, it can enhance the strength and hardness of the coating film, while improving its hydrophobic properties, so that the material has good chemical corrosion resistance.
[0107] The above description is only an exemplary embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A soft ceramic material that is both water and fire resistant, characterized in that: The raw materials of the water- and fire-resistant soft porcelain material include the following components: inorganic powder, modified polymer emulsion, surfactant, modified inorganic nanomaterial, curing agent, dispersant, film-forming aid, fiber and waterproofing agent, wherein the modified polymer emulsion is prepared by blending at least two polymer emulsions, and the mixture is mixed with the surfactant to undergo coupling reaction; The preparation step of the modified inorganic nano material includes modifying the inorganic nano material with a fluorinating agent.
2. The water- and fire-resistant soft ceramic material according to claim 1, characterized in that: The raw materials of the water- and fire-resistant soft porcelain material are calculated by weight, and the raw materials of the water- and fire-resistant soft porcelain material include the following components: 100-105 parts of inorganic powder, 12-25 parts of modified polymer emulsion, 0.3-9 parts of surfactant, 5-10 parts of modified inorganic nanomaterial, 0.1-0.4 parts of curing agent, 0.1-0.4 parts of dispersant, 0.1-0.4 parts of film-forming aid, 0.1-0.4 parts of fiber and 0.1-0.4 parts of waterproofing agent.
3. The water- and fire-resistant soft ceramic material according to claim 1, characterized in that: The inorganic powder includes quartz powder, kaolin, diatomaceous earth, alumina, waste residue, modified aluminum hydroxide and the modified magnesium hydroxide; and / or, The modified polymer emulsion includes at least two of polyurethane emulsion, acrylic emulsion and EVA emulsion; and / or, The surfactant includes at least one of a titanate coupling agent, an aluminate coupling agent, a silane coupling agent, and liquid paraffin; and / or, The modified inorganic nanomaterial includes at least one of nano calcium carbonate, nano titanium dioxide and nano silicon dioxide; and / or, The curing agent includes aziridine or polycarbodiimide; and / or, The dispersant comprises SN 5040; and / or, The film-forming aid includes alcohol ester 12; and / or, The fibers include polypropylene fibers modified by coupling agents, carbon fibers modified by coupling agents, and glass fibers modified by coupling agents; and / or, The waterproofing agent includes an organic silicon waterproofing agent.
4. The water- and fire-resistant soft ceramic material according to any one of claims 1 to 3, characterized in that: The inorganic powder includes waste residue, and the waste residue includes fly ash microbeads, mineral powder or silica ash.
5. The water- and fire-resistant soft ceramic material according to any one of claims 1 to 3, characterized in that: The inorganic powder includes an alkaline activator, and the amount of the alkaline activator added is 2-4% of the inorganic powder; and / or, The inorganic powder comprises quartz powder, kaolin, diatomaceous earth, alumina, waste residue, modified aluminum hydroxide and modified magnesium hydroxide, wherein the mass ratio of the quartz powder, the kaolin, the diatomaceous earth, the alumina, the waste residue, the modified aluminum hydroxide and the modified magnesium hydroxide is (2-4): (2-3): (2-3): (1-2): (1-3): (1-2): (0-1) 。 6. A method for preparing a water- and fire-resistant soft ceramic material as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S10, mixing and heating the inorganic powder and the surfactant to obtain a modified inorganic powder; S20, mixing the modified polymer emulsion with the modified inorganic nanomaterial to obtain a first emulsion; S30, mixing the first emulsion with a curing agent, a dispersant, a film-forming aid, fibers and a modified inorganic powder to obtain a second emulsion; S40, drying the second emulsion and demoulding to obtain a water- and fire-resistant soft ceramic material.
7. The method for preparing the water- and fire-resistant soft ceramic material according to claim 6, characterized in that: In step S10, the heating temperature is 70 to 150°C.
8. The method for preparing the water- and fire-resistant soft ceramic material according to claim 6, characterized in that: Step S40 includes: drying the second emulsion at 40-50° C. for 5 hours, adjusting the temperature to 80-150° C. for baking for 4-10 hours, and demolding to obtain a water- and fire-resistant soft ceramic material.